Richardson, Bill (London, 2013)
2013 "Richardson, Bill", 2013, HistoryTalk Bill describes his childhood and parents in Acton. He talks about his early work as a toolmaker at Napiers on Acton High Street in west London during World War II eg Production Committees. He describes the job of a toolmaker in the aero industry , developing the technical aspects on the shopfloor, defining a toolmaker as a craftsman making master tools. He had qualified for a place at a County School but had to leave school as one of a family of eleven children. He went to work on the Park Royal industrial estate at Beetensons (?)making car components and describes the various grades in the production system, doing piecework. He moved to Hoovers on the Western Avenue in 1947- 48 for 15 years after a dispute over the rate for the job (earning about £5.00 per week). He describes Hoovers as a fairly liberal firm. He later worked on London Transport for 13 years from 1970 1984 in the tool- room on the bus repair side at Chiswick Works (since closed down). He also worked at Aldenham Works in Hertfordshire.